2016
DOI: 10.1016/j.fertnstert.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Antimüllerian hormone among women with and without type 1 diabetes: the Epidemiology of Diabetes Interventions and Complications Study and the Michigan Bone Health and Metabolism Study

Abstract: Structured Abstract Objective To compare concentrations of anti-Müllerian hormone (AMH) in women with and without type 1 diabetes. Design Cross-sectional analysis of longitudinal studies adjusting for repeated measures Setting Michigan Bone Health and Metabolism Study (MBHMS), a community-based population and the Epidemiology of Interventions and Complications Study (EDIC), an observational cohort of women with type 1 diabetes. Participants Women who were aged 30–45 years and had not undergone oophorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
2
20
0
2
Order By: Relevance
“…However, not all studies have reported patterns of early follicular development followed by later follicular decline. In a comparison of women with and without T1DM, Kim et al found that women with T1DM had lower AMH concentrations than age-matched counterparts initially, but concentrations were similar in later reproductive age[25]. This suggests that T1DM may negatively affect reserve, but in earlier rather than in later reproductive years.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all studies have reported patterns of early follicular development followed by later follicular decline. In a comparison of women with and without T1DM, Kim et al found that women with T1DM had lower AMH concentrations than age-matched counterparts initially, but concentrations were similar in later reproductive age[25]. This suggests that T1DM may negatively affect reserve, but in earlier rather than in later reproductive years.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that premenopausal women with type 1 diabetes may have fewer available ovarian follicles than women without diabetes. Data conflict regarding ovarian reserve as measured by serum anti-Müllerian hormone: whereas several studies reported lower levels of serum anti-Müllerian hormone in women with diabetes than in those without type 1 diabetes (24,25), others found no difference by diabetes status (26,27). It is possible that women with type 1 diabetes experience a more rapid decline in ovarian reserve before menopause (24), which could lead to the discrepancies seen in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no published studies that compare AMHRII expression in diabetic female patients and no molecular explanation of this observation was proposed. There are, however, studies presenting lower concentrations of serum AMH in type 1 diabetic female patients [ 39 ]. Lower concentrations were also reported in PCOS patients with diabetes, in comparison with PCOS patients without diabetes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower concentrations were also reported in PCOS patients with diabetes, in comparison with PCOS patients without diabetes [ 40 ]. Attempts at describing this correlation suggested that vascular damage lowers the ovarian reserve [ 39 ]. Another study conducted in a group of premenopausal women with diabetes did not prove that markers of early vascular damage correlated with the level of AMH [ 41 ].…”
Section: Discussionmentioning
confidence: 99%